Brain transcriptome wide association study (TWAS) implicates 8 genes across 6 loci in Alzheimer's disease: Genetics: Genetics and omics of AD I. (7th December 2020) - Gockley, Jake; Montgomery, Kelsey S.; Poehlman, William L.; Liu, Yue; Gerasimov, Ekaterina S.; Greenwood, Anna K.; Wingo, Aliza P.; Wingo, Thomas S.; Mangravite, Lara M.; Logsdon, Benjamin A.
Abstract: Background: Alzheimer's disease (AD), an incurable neurodegenerative disease, currently affects 1.75% of the United States population, with projected growth to 3.46% by 2050. Common genetic variation linked transcript expression differences which confer AD‐risk isl necessary to elucidate AD mechanism and develop therapeutic interventions. We modified the FUSION pipeline to ingest expression from multiple neocortical regions, provide a set of 6780 gene weights which is abstracatable across the neocortex, and leverage these to find 8 genes with associated AD risk validated through summary mendelian randomization (SMR) utilizing IGAP summary statistics. Method: Ancestry matching based on 1000 genomes supervised clustering utilizing yielded 2003 Northern European (CEU) profiles, 888 of which had matched genotype‐RNASeq profiles. Expression Z‐scaling within‐tissue allowed weights to be trained from multiple Neo‐cortical tissues (TCX = 248, FP = 50, IFG = 41, STG = 34, PHG = 34, DLPFC = 461) after RNA‐Seq profiles were corrected for covariate and AD diagnosis stage within study. Result: Cis‐variant architecture alone was informative to train weights for 6780 (49.67%) autosomal genes, the majority of which signficantly correlated with gene expression; FDR < 5%: N = 6775 (99.92%), Bonferroni: N = 6716 (99.06%). The median correlation to observed gene expression was 0.2176 (IQR = 0.179‐0.277). Validation rate in 621 matched genotype to RNASeq profiles from the CommonMind Consortium (CMC) was (71.08%) in DLPFC and (22.52%) in anterior cingulate cortex (ACC) profiles. After correction for joint conditional probability (JCP) and SMR validation, 8 genes were significantly associated with AD (FDR < 0.05); APOC1 (JCP = 2.22e‐22, SMR = 3.41e‐4), EED (JCP = 3.373e‐5, SMR = 2.50e‐4), CD2AP (JCP = 2.96e‐5, SMR = 2.66e‐4), CEACAM19 (JCP = 3.27e‐5, SMR = 1.00e‐2), CLPTM1 (JCP = 4.04e‐3, SMR = 2.58e‐3), MTCH2 (JCP = 0.011, SMR = 3.32e‐6), TREM2 (JCP = 0.021, SMR = 2.64e‐3), KNOP1(JCP = 0.039, SMR = 2.50e‐4). Conclusion: We provide evidence of cis‐genetic variation confering AD risk through 8 genes across six distinct genomic loci. Moreover, we provide a valuable resource to the community in the form of predictive gene expression weights that are abstractable to multiple neocortical regions and neuronal phenotypes.